Rethinking informed consent in the time of COVID-19: An exploratory survey - De Sutter, Evelien; Lalova-Spinks, Teodora; Borry, Pascal; Valcke, Peggy; Kindt, Els; Negrouk, Anastassia; Verhenneman, Griet; Derèze, Jean-Jacques; Storme, Ruth; Huys, Isabelle (Frontiers in Medicine, 2022)
Background: Owing to the infectious nature of COVID-19, alternative solutions, such as electronic informed consent (eIC), needed to be implemented to inform research participants about study-related information and to obtain their consent. This study aimed to investigate stakeholders’ experiences with alternative consenting methods as well as their views on any regulatory or legal guidelines for eIC implementation in clinical research. Results may serve as the cornerstone to rethink the informed consent process in clinical research. Methods: This study consisted of an online survey among three stakeholder groups across European Union (EU) Member States and the United Kingdom. The stakeholder groups included i) investigators, ii) data protection officers or legal experts working in the pharmaceutical industry, academia, and academic biobanks, and iii) ethics committee members. Data collection occurred between April and December 2021. The data collected were analyzed using descriptive and inferential statistics. Results: The online survey was completed by 191 respondents, of whom 52% were investigators. Respondents were active in 24 out of the 27 EU Member States and the United Kingdom. The majority of each stakeholder group considered validated electronic methods moderately or extremely useful to re-consent previously enrolled research participants upon study amendments or to obtain consent from COVID-19 patients. Nevertheless, this exploratory survey identified that only 13% of data protection officers/legal experts, 26% of investigators, and 41% of ethics committee members had experience with eIC. In addition, results suggest that the legal acceptance of eIC across EU Member States and the United Kingdom is variable and that a definition of eIC, issued by national law or policy, is rarely available. The results also showed that the COVID-19 pandemic brought additional challenges to inform participants and to obtain their consent; for example, related to travel restrictions. Conclusion: A number of alternative consenting methods were recommended, for example by the European Medicines Agency, to ensure clinical study continuation during the COVID-19 pandemic. Although stakeholders support the use of eIC in clinical research, it seems that the experience with eIC is low. To harmonize eIC practices as much as possible, further investments in multi-stakeholder, multi-national guidance are needed.